When I run this program, I get no solution at the end, but there should be 
a solution ( I believe). Any idea what I am doing wrong? If you take away 
the Q from e2 equation it seems to work correctly.

#!/usr/bin/pythonfrom sympy import *

a,b,w,r = symbols('a b w r',real=True,positive=True)
L,K,Q = symbols('L K Q',real=True,positive=True)

e1=K
e2=(K*Q/2)**(a)
print solve(e1-e2,K)

It works if we do the following:

   - Set Q=1 or,
   - Change e2 to e2=(K**a)*(Q/2)**(a)

I would still like it to work in the original way though, as my equations 
are more complicated than this.

-- 
You received this message because you are subscribed to the Google Groups 
"sympy" group.
To unsubscribe from this group and stop receiving emails from it, send an email 
to sympy+unsubscr...@googlegroups.com.
To post to this group, send email to sympy@googlegroups.com.
Visit this group at http://groups.google.com/group/sympy.
For more options, visit https://groups.google.com/groups/opt_out.

Reply via email to